Analyzing the Policy Implementation of the Sepeda Keren Program in East Java: A Van Meter and Van Horn Framework - Laily Purnawati; Yunita Intan Hapsari; Angkasawati (WISE Pendidikan Indonesia, 2026)
This study analyzes the implementation of the Women, Disabilities, Children, and Other Vulnerable Groups School Program (SEPEDA KEREN) in Durenan Subdistrict, Trenggalek Regency. Initiated through Regional Regulation No. 5/2023, this program serves as an innovative response to the high subdistrict poverty rate of 18.7%. Employing the policy implementation framework of Van Meter and Van Horn (1975), this research focuses on the dynamics of vulnerable group empowerment at the grassroots level—a dimension often overlooked by conventional policy evaluations. By combining the perspectives of government officials, legislators, and community members, a qualitative approach was utilized to gather data through observations, documentation, and semi-structured in-depth interviews with 10 purposively selected key informants. The data were analyzed through thematic coding based on theoretical indicators and verified using data and source triangulation. The findings reveal that the program's implementation has been relatively successful across three primary variables: the clarity and acceptance of policy standards among implementers, high normative commitment from mentors and cadres, and robust political support. However, structural constraints persist in the remaining three variables: horizontal inter-agency coordination remains limited to administrative formalities, a critical shortage of specialized human resources for disability support endures, and the program has yet to establish adequate downstream market connections for its alumni.